SURVIVOR SKILLS: AUTHENTICITY, REPRESENTATION AND WHY I WANT TO TEACH REALITY TV - Friedman, May (Dialogue, 2(1), 2015)
This paper will consider the pedagogical potential in constructing a class on the phenomenon of reality television by exploring the possibilities and pitfalls of a shared viewing of these “texts” as a site of critical engagement with popular culture. A course on reality TV would require a deep analysis of the topics of representation, authenticity, and audience reactions. The course I would like to teach would also consider the ways that reality TV is simultaneously emblematic of, and contributes to, the foregrounding of neo-liberal discourses. This paper addresses some of the pedagogical implications of an analysis of reality TV by considering the above themes in greater detail. I see the creation of a post-secondary class on reality TV as pedagogically radical in both form and content, as a site where new ideas can be applied to shifting and unstable terrain. In challenging the primacy of high culture as the only worthy area of analysis, in viewing one of the most debased forms of popular culture as academically rich, I hope to help my undergraduate students build bridges between what they think about in school and what they do at home. I see such a class as an exciting explosion of the binaries of high and low culture, public and private space, and truth and fiction. Keywords: Reality Television, Engaged Pedagogy, Popular Culture, Representation, Authenticity, Neoliberalism, Social Work, Critical Discourse Analysis
Keywords: Reality Television; Type of access: Open Access; Critical Discourse Analysis; Neoliberalism; Popular Culture